Penggunaan Obat Kuat Bagi Pasangan Suami Istri Menurut Teori Mashalahah - Haikal, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2023)
The realization of a harmonious family with the fulfillment of the needs of husband and wife is the hope of every couple. However, when problems arise in meeting these needs, couples must find ways to ensure that it does not have a significant impact on the continuity of the household. One way is by using aphrodisiacs. This study aims to examine the use of aphrodisiacs to fulfill the needs of couples in the context of maslahah (benefit). The method used is qualitative with a library research approach. The results of the study indicate that there is maslahah in the use of aphrodisiacs to fulfill the needs of couples, and the level is considered hajiyat (necessary).